2011
DOI: 10.1111/j.1439-0418.2011.01644.x
|View full text |Cite
|
Sign up to set email alerts
|

Post‐teneral nutrition as an influence on reproductive development, sexual performance and longevity of Queensland fruit flies

Abstract: Adult Queensland fruit flies, Bactrocera tryoni (Froggatt), require adequate post‐teneral nutrition to complete reproductive development, to perform sexually and for maximum longevity. Recent research has focussed on nutritional requirements of adults released in sterile insect technique (SIT) programmes that are used to manage these pests. Several studies have suggested benefits of providing yeast hydrolysate (YH) in addition to sugar during the 24‐ to 48‐h pre‐release holding period. Current evidence suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 78 publications
(216 reference statements)
0
39
0
Order By: Relevance
“…Because immature flies are released in Qfly SIT, the ability of released flies to mature in the field before numbers are reduced by mortality can be an important determinant of how many sterile males are available to mate with wild females. Laboratory, field cage, and open field trials have reported positive effects of pre‐release YH supplementation on maturation, mating performance and survivorship of male Qfly . Findings of the present study indicate that substantial additional advantages may accrue through pre‐release supplementation with RK together with YH.…”
Section: Discussionmentioning
confidence: 56%
“…Because immature flies are released in Qfly SIT, the ability of released flies to mature in the field before numbers are reduced by mortality can be an important determinant of how many sterile males are available to mate with wild females. Laboratory, field cage, and open field trials have reported positive effects of pre‐release YH supplementation on maturation, mating performance and survivorship of male Qfly . Findings of the present study indicate that substantial additional advantages may accrue through pre‐release supplementation with RK together with YH.…”
Section: Discussionmentioning
confidence: 56%
“…Unfortunately, long‐term mass‐rearing reduces the overall mating competitiveness of male fruit flies (Cayol, ), necessitating the release of very large numbers of males which adds substantially to the cost of SIT. Reduced male mating performance in many tephritids can be overcome by improving colony management (Robinson & Hendrichs, ) and the adult diet (Pereira et al ., ; Taylor et al ., ) as well as by exposing sterile males to certain chemicals, such as ME for many of the Bactrocera spp. (Shelly, ; Shelly et al ., 2010 Pereira et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…The ratio of protein to carbohydrates in dry diets provisioned early in adult life contributed to male sexual performance and affected survival in a dose-dependent manner in A. fraterculus, A. ludens, A. obliqua and B. tryoni (Prabhu et al 2008;Gó mez et al 2013;Liedo et al 2013;Segura et al 2013; (Yuval et al 2007;Gavriel et al 2010;Taylor et al 2013) In the laboratory, protein-fed males lived significantly longer than sugar-fed males of B. cucurbitae and B. tryoni (Haq et al 2010b;Taylor et al 2013). The same was found in A. ludens and A. obliqua when the sugar/yeast ratio was 9:1 or 24:1, but not with the 3:1 ratio ) Inhibition of remating Feeding on a nitrogen-rich food significantly improved the ability of sterile males to inhibit female remating in A. fraterculus, B. tryoni and C. capitata (Harmer et al 2006;Radhakrishnan and Taylor 2007;Gavriel et al 2009;Segura et al 2013 The contribution of microorganisms to fitness of non-sterile Bactrocera oleae and C. capitata was established Ben-Yosef et al 2008aYuval et al 2013) Manipulating the microflora of sterile males suggests that probiotic supplements could improve male sexual performance in C. capitata (Niyazi et al 2004;Behar et al 2005Behar et al , 2008aBen-Ami et al 2010) these phenomena, to extend them to other species, and to transfer and validate them under large-scale conditions of action SIT programmes.…”
Section: Semiochemical Supplementsmentioning
confidence: 99%